Karakteristik Protein Daging Sapi Bali Dan Wagyu Setelah Direbus (THE PROTEIN CHARACTERISTICS OF BALI AND WAGYU BEEF BOILED) - Subagyo, Widodo Cipto; Suwiti, Ni Ketut; Suarsana, I Nyoman (Buletin Veteriner Udayana, 2015)
The protein is one of the meat component. The exestence of the protein and amino acid willdetermine the charateristic and the quality of meat. The aim of the reseach is to know thecharacteristic of protein bands, composition and consentration of amino acid in bali and wagyubeef after boiled. This research was used bali and wagyu beef wich taken from femoralis biceps muscle. Meat size of 1x1x1 cm was boiled for 15 and 30 minutes, five g of each beef (bali andwagyu) extracted, subsequently analized using the SDS-PAGE (sodium dodecyl sulfatpolyacrilamide gel electrophoresis) method, in order to know the bands of  protein. While theHPLC (high performance liquid chromatography) metode was used to analize the amino acid. Theresults showed that boiled for 15 minutes of bali and wagyu beef appear five bands of protein bothbali and wagyu beef. While boiling for 30 minutes show four protein bands for bali beef, and just 3three protein bands for wagyu beef respectively. Results of HPLC showed both bali and wagyubeef contains nine types of essensial amino acid and six types of non-essensial amino acid. After 30minutes of boiled, the essensial amino acid decreases as much as 56,65% for bali beef and 27,37%for wagyu beef. On the other hands, the consentration of non-essensial amino acid for bali beefdecreases as much as 63,05%  and wagyu beef 67,17% respectively.
Keywords: bali and wagyu beef; protein bands; amino acid; HPLC; SDS-PAGE